Application of Critical Literacy to Anticipate the Spread of Fake News by Residents of Karang Taruna Medan Amplas - Zulfan; Rangkuti, Rahmadsyah (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
The purpose of this community service activity is to anticipate the spread of false news and acts of hate speech committed by youth members of the Medan Amplas District, Medan City. Spreading false news and acts of hate speech is a crime that has recently become increasingly widespread and has been in the spotlight of various groups. This is due to the inevitability that Indonesia is a developing democratic country. Moreover, this country is a country whose population is a multicultural society, and is very vulnerable to the threat of social conflict caused by the act of spreading false news and acts of hate speech. As a multicultural country, the reality of diversity is a potential that has two sides. It can be positive or negative, depending on how it is managed. To manage socio-cultural diversity, it can be done by avoiding the spread of fake news and acts of hate speech. Prevention of these two things can be done by utilizing critical reading strategies. Therefore, specifically, this service activity is targeted to contribute to partners' knowledge and understanding of critical language awareness to prevent the spread of false news and hate speech. This method of community service is carried out in the form of field counseling through lectures on the use of reading strategies and critical literacy to prevent the spread of false news. The results of this service activity show that the residents of Karang Taruna, Medan Amplas Sub-district, already know about the problems of multicultural society in Indonesia and have succeeded in applying critical literacy strategies.